Investigation of bacterial diversity in Cajanus cajan-planted gangue soil via high-throughput sequencing. Issue 1 (1st January 2021) - Han, Shimin; Wang, Yuexia; Li, Yuan; Shi, Kaiyi
ABSTRACT: The ecological restoration of coal gangue can be achieved by planting Cajanus cajan (pigeon pea) because of its developed root system. The close relationships soil microorganisms have with plants are crucial for improving soil composition; the soil composition affects nutrient absorption. The microbial composition and function of soil planted with C. cajan in reclaimed land were compared with soil that was not planted with C. cajan (the control). Results showed that the dominant microflora in the soil significantly changed after planting C. cajan . Before planting, the dominant microflora included members of the phyla Sulfobacteria and Acidobacteria. After planting, the dominant microflora contained bacteria from phyla and classes that included Actinobacteria, Acidimicubia, Thermoleophilia, and Anaerolineae . Additionally, there were significant differences in the bacterial composition of each layer in soils planted with C. cajan . Principal component analysis revealed that the interpretation degrees of the results for PC2 and PC3 axes were 10.46% and 3.87%, respectively. The dominant microflora were Vicinamibacterales, Nocardioides, and Arthrobacter in the surface soil; Actinophytocola and Sphingomonas in the deep soil; and Sulfobacillus and Acidimicrobium in the mixed-layer soil. Function prediction analysis using the bioinformatics software package PICRUSt revealed that the abundance of operational taxonomic units corresponding to sigma 54-specific transcriptional regulators, serine threonine protein kinase, and histidine kinase increased by 111.2%, 56.8%, and 47.4%, respectively, after planting C. cajan . This study provides a reference for interactions among microorganisms in reclaimed soils for guiding the development and restoration of waste coal gangue hills.